Effect of low-energy extracorporeal shock wave on vascular regeneration after spinal cord injury and the recovery of motor function - Wang L (Dove Medical Press, 2016)
Lei Wang, Yuquan Jiang, Zheng Jiang, Lizhang Han Department of Neurosurgery, Qilu Hospital of Shandong University, Jinan, People’s Republic of China Background: Latest studies show that low-energy extracorporeal shock wave therapy (ESWT) can upregulate levels of vascular endothelial growth factor (VEGF). VEGF can ease nervous tissue harm after spinal cord injury (SCI). This study aims to explore whether low-energy ESWT can promote expression of VEGF, protect nervous tissue after SCI, and improve motor function.Methods: Ninety adult female rats were divided into the following groups: Group A (simple laminectomy), Group B (laminectomy and low-energy ESWT), Group C (spinal cord injury), and Group D (spinal cord injury and low-energy ESWT). Impinger was used to cause thoracic spinal cord injury. Low-energy ESWT was applied as treatment after injury three times a week, for 3 weeks. After SCI, the Basso, Beattie, and Bresnahan (BBB) scale was used to evaluate motor function over a period of 42 days at different time points. Hematoxylin and eosin (HE) staining was used to evaluate nerve tissue injury. Neuronal nuclear antigen (NeuN) staining was also used to evaluate loss of neurons. Polymerase chain reaction was used to detect messenger RNA (mRNA) expression of VEGF and its receptor fms-like tyrosine kinase 1 (Flt-1). Immunostaining was used to evaluate VEGF protein expression level in myeloid tissue.Results: BBB scores of Groups A and B showed no significant result related to dyskinesia. HE and NeuN staining indicated that only using low-energy ESWT could not cause damage of nervous tissue in Group B. Recovery of motor function at 7, 35, and 42 days after SCI in Group D was better than that in Group C (P<0.05). Compared with Group C, number of NeuN-positive cells at 42 days after SCI increased significantly (P<0.05). The mRNA levels of VEGF and Flt-1 and VEGF expression at 7 days after SCI in Group D were significantly higher than those in Group C (P<0.05).Conclusion: Low-energy ESWT promotes expression of VEGF, decreases secondary damage of nerve tissue, and improves recovery of motor function. It can be regarded as one mode of clinical routine adjunctive therapy for spinal injury. Keywords: spinal injury, impact wave, VEGF, Flt-1, nerve protection